Rothe’s Method for Phase Field Problem - Vaz, C. (Trends in Computational and Applied Mathematics, 2007)
In this paper, a phase-field model is considered. Analysis of a time discretization for an initial-boundary value problem for this phase-field model is presented. Convergence is proved and existence, uniqueness and regularity results are derived.